2023
DOI: 10.4018/978-1-6684-6961-3.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment Challenges of First-Year Students

Abstract: This chapter presents an overview of the psychological adjustment challenges of first-year students. A review of the literature has been carried out to address the main research question of this study: “What are the psychological adjustment challenges that first-year university students face?” The chapter discusses the most common factors that negatively affect adjustment to universities such as stress, anxiety and fears, depression, self-esteem, the importance of self-esteem, signs of high and low self-esteem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This variable is considered an important indicator of academic success and permanence of students (Pérez et al, 2020). For the achievement of an adequate integration into Cobo-Rendón et al 10.3389/feduc.2023.1303765 university life, empirical evidence has shown that contributing to the adaptation of young student's elements such as emotions, wellbeing, and perception of support is essential for their development, and this is because during the transition processes students experience emotions such as anxiety, hopelessness, worry, and stress (Chan and Rose, 2023;Hako et al, 2023). Adaptation to university life is critical to permanence and depends, from the student's point of view, on the social experiences and resources that the student uses at the university (Van Rooij et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This variable is considered an important indicator of academic success and permanence of students (Pérez et al, 2020). For the achievement of an adequate integration into Cobo-Rendón et al 10.3389/feduc.2023.1303765 university life, empirical evidence has shown that contributing to the adaptation of young student's elements such as emotions, wellbeing, and perception of support is essential for their development, and this is because during the transition processes students experience emotions such as anxiety, hopelessness, worry, and stress (Chan and Rose, 2023;Hako et al, 2023). Adaptation to university life is critical to permanence and depends, from the student's point of view, on the social experiences and resources that the student uses at the university (Van Rooij et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Students face numerous new experiences that are entirely unfamiliar, and they are expected to perform well in this unfamiliar environment. The most common obstacles students face are schedule creation, time management, homesickness, academic stress, and forming new social connections (Hako et al, 2023). Unsurprisingly, college students routinely display higher levels of psychological distress than most other groups, which manifests depression, anxiety, stress, and poor sleep quality (Ferrari et al, 2022;Saleh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This variable is considered an important indicator of academic success and permanence of students (Pérez et al, 2020). For the achievement of an adequate integration into university life, empirical evidence has shown that contributing to the adaptation of young student's elements such as emotions, wellbeing, and perception of support is essential for their development, and this is because during the transition processes students experience emotions such as anxiety, hopelessness, worry, and stress (Chan and Rose, 2023;Hako et al, 2023). Adaptation to university life is critical to permanence and depends, from the student's point of view, on the social experiences and resources that the student uses at the university (Van Rooij et al, 2018).…”
Section: Introductionmentioning
confidence: 99%